Species-specific sensitivity of three microalgae to sediment elutriates. (April 2020) - Gallo, A.; Guida, M.; Armiento, G.; Siciliano, A.; Mormile, N.; Carraturo, F.; Pellegrini, D.; Morroni, L.; Tosti, E.; Ferrante, M.I.; Montresor, M.; Molisso, F.; et al.
Abstract: Microalgae are considered good bioindicators of marine environmental quality. Frequently, they are used to investigate the toxicity of sediment elutriates, but their sensitivity is disputed. This paper compared the sensitivity of Phaeodactylum tricornutum (diatom), Skeletonema costatum (diatom), and Dunaliella tertiolecta (green alga), analyzing 257 samples of elutriates (1:4 sediment: water ratio), considering growth inhibition (72 h) as the reference endpoint and sediment chemical (metals, metalloids and polyaromatic hydrocarbons) and grain size. Results of the toxicity tests showed that the microalgae sensitivity was not correlated. The integration of chemical data did not allow to discriminate toxicity effects but contributed to highlight that D. tertiolecta was the most sensitive microalgae (no cell wall) followed by P. tricornutum and S. costatum . Further analysis, including lines of evidence and weight of evidence approaches to calculate risk quotients of elutriate samples, confirmed these results. Graphical abstract: Image 1 Highlights: Sensitivity of three microalgae to elutriates from highly contaminated sediments is compared. Uni- and multivariate analyses did not highlight any significant correlation among species. Single chemicals and granulometry did not facilitate samples ranking. Species sensitivity to elutriates was: S. costatum  <  P. tricornutum  <  D. tertiolecta .